Nowelizacja Kodeksu Pracy z 2023 roku transponująca dyrektywę w sprawie równowagi między życiem zawodowym a prywatnym rodziców i opiekunów w Polsce jako element budowy państwa dobrobytu. Analiza ideologicznych podstaw procesu decyzyjnego - Szczepański, Jarosław; Nadolska, Jadwiga (PRAWO i WIĘŹ, 2026)
The work-life balance directive and its transposition process have become key elements in the development of a regulatory welfare state within the European Union. This case study aims to trace the legislative process of transposition in Poland. By supplementing the decision-making analysis with an ideological component (the welfare state doctrine), we can verify whether the transposition and subsequent implementation of the directive in Poland was also intended to expand the welfare state.